RELATIVE STRICT LLABILITY FOR THE PURPOSE OF THE CONSTITUTIONAL ADMINISTRATIVE REFORM - Facundo Niño de Guzmán, Luis Miguel (2019)
In this article, the author performs an analysis of the constitutionality of the relative strict liability in the sanctioning administrative law, because although at the legal level the LPAG has enshrined the exceptionality of strict liability, however our Constitutional Court has always enshrined the prohibition of strict liability for being incompatible with the principle of culpability. In that sense, various points such as the Philosophy of Law, General Theory of Law, Range of Guilt Principle, Comparative Law, among other aspects, will be analyzed in order to be able to propose a constitutional reform in order to specify the sanctioning authority of the Administration Public and constitutionalize the exceptionality of the relative strict responsibility with its respective law of constitutional development.